ASTAR 2000 2004, AAMP 2002 キャンペーン ノ コウクウキ カンソク デ エラレタ ホッキョクイキ タイリュウケン ニ オケル シュンキ エアロゾル ノ サンラン ケイスウ リュウケイ ブンプ オヨビ ユソウ ケイタイ - 山形, 定; ヤマガタ, サダム; 原, 圭一郎; ハラ, ケイイチロウ; 松木, 篤; マツキ, アツシ; Yamagata, Sadamu; Hara, Keiichiro; Matsuki, Atsushi (2010)
P(論文) アークティックヘイズの特性を解明するためにおこなわれた3つの観測キャンペーン(ASTAR 2000,AAMP 2002,ASTAR 2004)で,エアロゾルの散乱係数,粒径分布などの航空機観測をおこなった.いずれのキャンペーンにおいてもエアロゾル粒子をステンレス製インレットから客室内に導入し,ディフューザーで減速後に各測定装置に分配した.エアロゾルの光学的散乱係数はアークティックヘイズ時,4000 m程度までの高度でそれ以上と際立った違いが認められた.これに対し,対流圏上層の散乱係数は,アークティックヘイズ期,清浄期でほぼ同じレベルであった.ヘイズ期にはエアロゾルの粒径分布は,清浄期のものよりも大きく,気塊が発生から長時間経っていることを示した. ヘイズ層の微細構造を明らかにするためおこなったカーテンフライトの結果,エアロゾルは等温位面を輸送されていることがわかった. Airborne aerosol measurements of the Arctic haze were carried out during three campaigns, Arctic Study of Tropospheric Aerosol and Radiation 2000 (ASTAR 2000), the Arctic Airborne Measurement Program 2002 (AAMP 2002) and ASTAR 2004. Aircraft used for the campaigns were Dornier for ASTAR 2000 2004 and Gulfstream II for AAMP 2002. For all measurements aerosol particles were introduced into the cabin through stainless inlets and distributed to several instruments via a diffuser. Scattering coefficient of aerosol particles measured with an integrating nephelometer during the Arctic haze period showed a distinct difference between the lower, i.e. up to around 4000 m, and higher troposphere. Meanwhile, scattering coefficients in higher troposphere during the Arctic haze were in the same degree with those after the Arctic haze. Size distribution obtained from the data of a particle counter indicates that aerosol particles in accumulation mode during the Arctic haze have larger geometric mean diameter than those after the haze season, which reflects the aged air mass in the Arctic haze. "Curtain flight" which was carried out to reveal the fine structure of the haze layer showed that aerosol particles are transported in the isentropic plane. departmental bulletin paper